Modifying PCDH19 levels affects cortical interneuron migration - Pancho, Anna; Mitsogiannis, Manuela D.; Aerts, Tania; Dalla Vecchia, Marco; Ebert, Lena K.; Geenen, Lieve; Noterdaeme, Lut; Vanlaer, Ria; Stulens, Anne; Hulpiau, Paco; Staes, Katrien; Van Roy, Frans; et al. (Frontiers in Neuroscience, 2022)
PCDH19 is a transmembrane protein and member of the protocadherin family. It is encoded by the X-chromosome and more than 200 mutations have been linked to the neurodevelopmental PCDH-clustering epilepsy (PCDH19-CE) syndrome. A disturbed cell-cell contact that arises when random X-inactivation creates mosaic absence of PCDH19 has been proposed to cause the syndrome. Several studies have shown roles for PCDH19 in neuronal proliferation, migration and synapse function, yet most of them have focused on cortical and hippocampal neurons. As epilepsy can also be caused by impaired interneuron migration, we studied the role of PCDH19 in cortical interneurons during embryogenesis. We show that cortical interneuron migration is affected by altering PCDH19 dosage by means of overexpression in brain slices and medial ganglionic eminence (MGE) explants. We also detect subtle defects when PCDH19 expression was reduced in MGE explants suggesting that the dosage of PCDH19 is important for proper interneuron migration. We confirm this finding in vivo by showing a mild reduction in interneuron migration in heterozygote, but not in homozygote PCDH19 knockout animals. In addition, we provide evidence that subdomains of PCDH19 have a different impact on cell survival and interneuron migration. Intriguingly, we also observed domain-dependent differences in migration of the non-targeted cell population in explants, demonstrating a non-cell-autonomous effect of PCDH19 dosage changes. Overall, our findings suggest new roles for the extracellular and cytoplasmic domains of PCDH19 and support that cortical interneuron migration is dependent on balanced PCDH19 dosage.